Girinimbine for use as anti cancer agent. - Abdul, Ahmad Bustamam; Syam Mohan, Suvitha; Sukari, Mohd Aspollah; M., Sham Mohan (2011)
The present invention relates to novel means of treating hepatocellular carcinoma (HCC) using a natural compound isolated from the curry leave plant ? 3,3,5-trimethyl-11H-pyrano[3,2-a]carbazole (Girinimbine). The invention thus relates to methods for the prevention and/or treatment of proliferative diseases using the above compound. Further disclosed is the use of girinimbine as a food supplement and/or additive, specifically for daily intake to reduce the risk of developing such a disease. The invention further includes pharmaceutical compositions comprising the active compound, as well as the use of plant material for administration as a therapeutic or as a food supplement.